Understanding affordances and limitations in a language MOOC from an activity theory perspective - Napat Jitpaisarnwattana; Pornapit Darasawang; Hayo Reinders (The Asia-Pacific Society for Computers in Education (APSCE), 2022)
Abstract In the last decade, Language MOOCs have attracted a lot of interest for their potential to enhance language learning. However, how learners engage with MOOC environments and realise their benefits, remains unclear. The current study adopts activity theory (Engeström in J Educ Work 14:133-156, 2001) as a lens to comprehend the affordances and limitations in an LMOOC dealing with English presentation skills called Presentation@work. Data were collected via semi-structured interviews with 22 participants. The data were then analysed using thematic content analysis and triangulated with the participants' profiles using learning analytical procedures. The results showed that peer learning, personalisation, and social interaction opportunities were perceived as affordances by the participants, while lack of proficiency, lack of affinity, course content, and lack of teacher presence were seen as limitations. Relationships between the perceived affordances and limitations and different types of participants were also found. The findings demonstrate that the LMOOC activity system is dynamic and complex and that the learners play a central role in interacting with different aspects of the system. We conclude with a number of suggestions and implications for future LMOOC design, implementation and research.